Pencegahan Bahaya Narkoba Bagi Siswa Sma Negeri I Ungaran Melalui Edukasi Pathway Game â€œAnti Narkobaâ€ - Sikni Retno Karminingtyas; Nova Hasani Furdiyanti; Rissa Laila Vifta (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2020)
Drug abuse is currently a global emergency problem. World Drugs Reports 2018 published by the United Nations Office on Drugs and Crime (UNODC), said that as many as 275 million people in the world or 5.6% of the world's population (aged 15-64 years) have used drugs. The number of drug abuse among students in 2018 (from 13 provincial capitals in Indonesia) reached 2.29 million people. One of the groups of people who are prone to being exposed to drug abuse are those in the age range 15-35 years or the millennial generation. The purpose of this service is to increase students' knowledge about the types and types of drugs circulating in the community, so that students recognize the signs, characteristics and symptoms of people who are dependent on drugs, prevention and provide information about treatment measures if they have experienced drug dependence. The service activity was carried out in 2 stages, before the participants were given a questionnaire as a pretest and given education about drugs after the participants filled out the questionnaire as a postest. There were 37 students involved in the activity from SMA N 1 Ungaran Semarang Regency. The pretest results show that students' knowledge about the symptoms and effects of drug dependence, as well as information about how to overcome addiction is still lacking. However, the average student can answer the examples and types of drugs very well. After being given education about Drug Abuse in Adolescents, there was an increase seen from the pretest and posttest scores in terms of knowledge about drugs, symptoms and adverse effects of addiction, prevention and ways of overcoming drug dependence.abstrakPenyalahgunaan Narkoba saat ini menjadi masalah kedaruratan global. World Drugs Reports 2018 yang diterbitkan United Nations Office on Drugs and Crime (UNODC), menyebutkan sebanyak 275 juta penduduk di dunia atau 5,6 % dari penduduk dunia (usia 15-64 tahun) pernah mengonsumsi narkoba. Angka penyalahgunaan Narkoba di kalangan pelajar di tahun 2018 (dari 13 ibukota provinsi di Indonesia) mencapai angka 2,29 juta orang. Salah satu kelompok masyarakat yang rawan terpapar penyalahgunaan narkoba adalah mereka yang berada pada rentang usia 15-35 tahun atau generasi milenial. Tujuan dari pengabdian ini untuk meningkatkan pengetahuan siswa mengenai macam dan jenis Narkoba yang beredar di masyarakat, agar siswa mengenali tanda, ciri dan gejala dari orang yang mengalami ketergantungan terhadap Narkoba, pencegahan serta memberikan informasi mengenai tindakan penanganan bila sudah mengalami ketergantungan Narkoba. Kegiatan pengabdian dilaksanakan dalam 2 tahap, sebelum kegiatan peserta diberikan kuesioner sebegai pretest dan diberikan edukasi mengenai Narkoba setelah kegiatan peserta mengisi kuesioner sebagai postest. Siswa yang terlibat dalam kegiatan sejumlah 37 orang berasal dari SMA N 1 Ungaran Kabupaten Semarang. Hasil Pretes menunjukkan bahwa pengetahuan siswa mengenai gejala dan efek ketergantungan Narkoba, serta info mengenai cara penanggulangan ketergantungan masih sangat kurang. Akan tetapi rata-rata siswa dapat menjawab mengenai contoh dan jenis Narkoba dengan sangat baik. Setelah diberikan edukasi mengenai Penyalahgunaan Narkoba pada Remaja, terjadi peningkatan yang dilihat dari nilai pretes dan postes dalam hal pengetahuan tentang Narkoba, gejala dan efek buruk ketergantungan, pencegahan dan cara penanggulangan ketergantungan Narkoba.